Using physiological signals to measure operator's mental workload in shipping – an engine room simulator study. Issue 2 (4th May 2017) - Wu, Yanbin; Miwa, Takashi; Uchida, Makoto
ABSTRACT: Mental workload (MWL) is one of core elements of human factor construct reflecting arousal level, and its optimisation is crucial to maintain favourable operator functional state. However, sensible, reliable, and diagnostic measurement of MWL is essential for applications of adaptive aiding system design, usability testing, and seafarers' training. To develop robust MWL measures, 10 participants voluntarily participated in a simulator-based experiment study. During this study, the participants carried out standard four-level calibration tasks and simulated four-level maritime operation tasks, their heart rate and electroencephalogram (EEG) were continuously measured using a heart rate sensor and an ambulatory EEG device, which includes an accelerometer to distinguish signal corruption epochs induced by body movement artefact. After each task, NASA Task Load Index was collected as subjective measurement. One-way analysis of variance was used to test the sensitivity of MWL measures and Pearson's correlation coefficients were calculated. The significantly sensitive indices for n -back task and simulator-based maritime operation task were different, supporting the limited cognitive resource pool theory. EEG features showed higher sensitivity than heart-rate-related measures.